3D petroleum systems modelling as an exploration tool in mature basins: A study from the Central North SeaUK. (November 2021) - Badejo, S.A.; Fraser, A.J.; Neumaier, M.; Muxworthy, A.R.; Perkins, J.R.
Abstract: In this paper we apply two different geoscience tools: 3D petroleum systems modelling and the findings of rock magnetic analysis to a reassessment of the hydrocarbon migration system from the Upper Jurassic Kimmeridge Clay source rock to the reservoirs in the Tertiary Tay sandstones in the Western Central Graben in the Central North Sea, UK. The Tay Sandstones provide an excellent laboratory to study vertical and lateral migration in an area where the subsurface geology is well constrained by both modern 3D seismic data and a high density of cored wells. Mature, super basins such as the North Sea are often characterised by a perception that most of the oil has been found and there is no reason to update models even if new data has become available. During the course of this study, two untested prospects in the Gannet and Guillemot complexes have been identified and are presented as examples of the value generated by this type of integrated approach which promotes new thinking and critical testing of conventional models. Highlights: 3D Petroleum Systems Modelling of Central North Sea, UK. 3D seismic amplitude extractions used to discovery of untested hydrocarbon prospects, demonstrating the importance 3D petroleum systems modelling as an exploration tool in mature basins. Identification of two undrilled prospects in Gannet and Guillemot complexes. Mineral magnetic information used to aid hydrocarbon migration mapping.